Vermiwash: An effective nutritive blessing to crops - Nahar, K; Ashrafi, R; Haque, M A (Bangladesh Journal of Nuclear Agriculture, 2024)
Under alarming situation of poor soil health, reduction in produce, increase in incidences of pest and disease and environmental pollution due to the application of chemical fertilizers over a period, it is necessary to look for alternatives which are effective and eco-friendly for sustainable agriculture. Therefore, it is very important to seek alternative as a supplement for chemical fertilizers. To cope with these problems, vermiwash can play an important role in ensuring a sustainable agricultural system. A review was conducted on vermiwash to assess the characteristics, potentiality to use and ultimately beneficial effects in sustainable agriculture. Vermiwash is coelomic fluid extraction contains significant quantities of nutrients, a large beneficial microbial population, biologically active metabolites particularly gibberellins, cytokinins, auxins and group B vitamins which can be applied alone or in combination with organic or inorganic fertilizers, so as to get better yield and quality of diverse crops. Evidences proved that qualities of vermiwash depend on the used organic bed producing vermicompost. Vermiwash can serve as a valuable foliar spray, because it is a combination of earthworm mucous discharges, nutrients, microorganisms and plant growth promoting materials composed of excretory products and mucus secretions from earthworms and micronutrients from the organic molecules in the soil. These nutrients are absorbed and then transported to the leaves, shoots, and other parts of a plant. Application of vermiwash improves plant health, yield and nutritional quality. Vermiwash proves to be an effective fertilizer which contributes the growth of plants when sprayed directly as well as mixed with a definite ratio of vermicompost. It was also observed that the plants treated with vermiwash were disease resistant and no any worms like leaf eaters were seen on the leaves and other parts of plants. Vermiwash can be used as a substituent of commercial fertilizers available in the market. Vermiwash acts not only as a liquid organic fertilizer but also act as mild biocide. It can be used as an effective input in organic agriculture for both soil health and disease management for sustainable crop production with low cost which could be ensure food security. Bangladesh J. Nuclear Agric, 38(1): 21-40, 2024